The Effects of Urbanization and Economic Growth on The Igarapes of the Legal Amazon - Júnior, Antônio Pereira; Morales, Gundisalvo Piratoba; Beltrão, Norma Ely Santos; da Silva, Marília Palheta; de Jesus, Edmir dos Santos; Pereira, Lucimar Costa (Archives of Business Research, 2024)
This study shows the primary mechanisms causing alteration and degradation of water bodies. Data analysis on the condition of urban streams in the Eastern Amazon (53,8%) shows that Pará state is the most affected (n = 67,8%). The Almas and Mata Fome creeks in the Bengui neighborhood have undergone the most significant and irreversible environmental changes. Similarly, the Paragominas stream is experiencing ongoing harm due to urban and economic expansion. In the Western Amazon (46,1%) and Amazonas state (9.5±4.9), research on 16 streams says a housing shortage and an increase in peripheral development along these water bodies. Urbanization and economic growth are altering the ecosystem functions of urban streams, highlighting the urgent need for water management authorities in the legal Amazon region to focus on this issue.